Eros in the Apiary: Bees and Beehives in Early Modern Spanish Erotic Literature - Kuffner, Emily (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2020)
In early modern Spain, bees inspired admiration for their exemplary sexual life since their supposedly asexual spontaneous generation made them models of chastity within the hive, an idealized masculine commune led by a king bee. However, bee imagery frequently appears in erotic literature and an astonishing number of Spanish texts on prostitution, including two of the most iconic, La Celestina (1499) and La Lozana andaluza (1528), which apply apiary metaphors to a female procuress. This article examines this seeming contradiction to argue that apiary metaphors applied to prostitution dehumanize the prostitute as an exemplary beast in the bestiary tradition.